A Rare Case of Pseudoglucagonoma Syndrome Masquerading as Necrolytic Migratory Erythema - Nikita; Siba Prasad Dalai; Samir Sahu; Aswini Kumar Sahoo (Dr. Annil Mahajan, 2024)
Necrolytic migratory erythema (NME) is pathognomonic of glucagonoma syndrome associated with pancreatic neoplasm. Pseudoglucagonoma syndrome, which is extremely rare, refers to NME without a glucagon-secreting tumor. We describe a rare case of NME in a 45-year-old female who presented with a skin rash associated with scaling, cheilitis, glossitis, hair loss, and weight loss. Serum glucagon and serum zinc levels were normal. Skin biopsy was suggestive of necrolytic erythema migrans. Ultrasonography (USG) and computed tomography (CT) of the abdomen showed chronic pancreatitis. Resolution of lesions was observed with topical steroids, emollients, intravenous (IV) protein infusions, and other supplements.